2015
DOI: 10.1002/j.0022-0337.2015.79.12.tb06048.x
|View full text |Cite
|
Sign up to set email alerts
|

Instant Messaging in Dental Education

Abstract: Instant messaging (IM) is when users communicate instantly via their mobile devices, and it has become one of the most preferred choices of tools to communicate amongst health professions students. The aim of this study was to understand how dental students communicate via IM, faculty members' perspectives on using IM to communicate with students, and whether such tools are useful in the learning environment. After free-associating themes on online communication, two draft topic guides for structured interview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 23 publications
2
40
0
5
Order By: Relevance
“…Research has shown that, in [35]. Therefore, healthcare professionals have been discovering novel ways of providing services and teaching patients using mobile applications designed for use in the medical and dental fields [36]. These applications can be used to reduce patients' anxiety by educating patients about dental treatment and encouraging them to appropriately cope with the treatment [37].…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that, in [35]. Therefore, healthcare professionals have been discovering novel ways of providing services and teaching patients using mobile applications designed for use in the medical and dental fields [36]. These applications can be used to reduce patients' anxiety by educating patients about dental treatment and encouraging them to appropriately cope with the treatment [37].…”
Section: Discussionmentioning
confidence: 99%
“…However, the choice to provide ads-free service means that the consideration of monetization lay in other part of service or it has great resources to cover the service; and 4) another added advantages of WhatsApp over other messengers is that WhatsApp provides official web-based application that runs on Windows desktop environment. Additionally, it and can be used with the Chrome web based browser [13][14][15][16].…”
Section: Whatsappmentioning
confidence: 99%
“…Instant Messaging (IM) is a term used to describe the way users communicate instantly via their mobile devices, mainly smartphones, and it has become one of the most popular methods of communication amongst health professions 10 . Nowadays, the most popular messaging application is the WhatsApp Messenger, which has more than one billion users worldwide.…”
Section: Introductionmentioning
confidence: 99%